Incorporating Flood Inundation to Flood Risk Modeling - Lotero, Stephanya Salazar; Yong, Yan; Xie, Zhixiao; Teegavarapu, Ramesh; Su, Hongbo; Salazar, S.; Nagarajan, S.; Mitsova, D.; Meeroff, Daniel E.; Liu, Wiebo; Hoque, Mushfiqul; Bloetscher, Frederick; et al. (European Journal of Applied Sciences, 2024)
Coastlines are particularly vulnerable to flood under multiple conditions, including heavy precipitation, high sea levels and tropical storm surge. These conditions should be considered to assess and manage inundation with more effectiveness. As a part of a larger research effort to develop a watershed level screening tool to identify areas with potential for flooding, incorporating readily available data on topography, ground, and surface water elevations, tidal data for coastal communities, soils, and rainfall data. However, the most destructive impacts are more likely to be from storm surge – moving waves of water that inundate the coast. While SLOSH and other models can be used for this purpose, this effort reviewed prior storms to determine the impact surge actually has on coastal communities in South Florida. What was found was that in urban areas, a wedge of surge waters could be created. Likewise a wedge could be created for natural areas, although natural area extension was double that of urban areas. The wedge can be added to storm events, acting as inputs for Cascade 2001 software to calculate the headwater height for probabilities of inundation.